Pengaruh layanan kotak literasi cerdas terhadap minat baca masyarakat di Pangandaran - Almas Inti Kiasati; Heriyanto Heriyanto (Daluang, 2022)
Introduction. The level of public interest reading in West Java, especially in Pangandaran Regency is in the low category, this is due to the lack of facilities that support public interest reading. One of the efforts of West Java local government to increase the public interest reading is by distributing Kotak Literasi Cerdas services or Kolecer to several districts and cities in West Java, including in Pangandaran Regency. This study aims to analyze the effect of library services, namely Kotak Literasi Cerdas or Kolecer on public interest reading in Pangandaran Regency.